Deep Learning Pembelajaran Mendalam di Lembaga Pendidikan Islam: Literatur Review: Deep Learning Pembelajaran Mendalam di Lembaga Pendidikan Islam: Literatur Review - Selfia Zainur; Delli Marlina; Aprizaldi; Sumiarti; Hamzah Irfanda (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
This study aims to examine the application of Deep Learning in Islamic education, particularly in Madrasah Ibtidaiyah (MI) and Madrasah Tsanawiyah (MTs) institutions, as an integrative effort to develop the cognitive, affective, and psychomotor aspects of students. This study uses a qualitative method with a Literature Review approach, analyzing various recent findings from SINTA journals and other academic sources to explain the concepts, principles, and implementation of Deep Learning in Islamic Religious Education (PAI). The results of the study show that the three main principles of Mindful Learning, Meaningful Learning, and Joyful Learning play a significant role in building a more reflective, contextual, and enjoyable learning process. The application of Deep Learning in Islamic educational institutions not only strengthens the internalization of religious values but also improves students' critical thinking skills, learning motivation, and social-emotional skills. Additionally, this approach has been proven to have a positive impact on learning outcomes in the cognitive, affective, and psychomotor domains, making it suitable for strengthening the quality of PAI learning in madrasahs.